Evaluation of Program Design Crediamigo of the Northeast Bank: Social Inclusion and Market - Maria CÃlia Garcia Ferreira de Souza (2008)
The objective of this survey is to evaluate the drawing of a productive and controlled micro credit program from Banco do Nordeste do Brasil, Crediamigo Program, showing how a developing public bank implements a generation of yields with some micro credit politics. That attends to the society yearning and to the mission of the bank itself of develop the region and at the same time pays the invested capitals making possible the sustainability of public politics. To the theme development it was reached the origin of the microcredit in Brazil, through a historical and economical context of the country that culminates in a helpful situation to the genesis of Crediamigo Program. Besides, there is a development presentation in the financial institution âNordeste Bankâ, with national and international partnersâ support. At the end, there are related the results of the research that shows âBNBâ as a financial institution with a capable vocation of developing the region through the concession of a productive credit, that implementing its micro credit politics, banned several paradigms, so far had as absolute truths. It has being presented also the conclusion about the social reaching of CrediamigoProgram and its sustainability as productive and controlled micro credit politics